INTERMEDIATE LANGUAGE AND ARABIC LANGUAGE TEACHING ITS FOUNDATIONS AND PROBLEMS - Dr. Sayed Mohamed Ahmed Korayem; Dr. Mohammed Ali Abdul Wahed Awad (“ARAB TILI GLOBALLASHUV DAVRIDA: INNOVATSION YONDASHUVLAR VA O‘QITISH METODIKASI” MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2024)
Therefore, researchers in the field of language education and learning are constantly seeking to identify the latest and most useful methods in teaching a foreign language, and it was confirmed that this should be sought, and the challenges imposed by it in various fields; which necessitated looking for ways to meet these challenges, and re-evaluating many teaching methods, methods and strategies again, and here the problem of intermediate language arises as a method that is relied on in teaching foreign languages, and this problem raises many questions about the feasibility of using this method, or its uselessness, and whether teaching the Arabic language for non-native speakers calls for its use Or his negligence The research here seeks to answer these questions through a descriptive analytical approach that monitors the areas of intermediate language use in the field of teaching foreign languages, highlights the pros or cons of this use, and balances them; to come up with convincing answers to the questions posed